A systematic literature review of education for Generation Alpha - Alena Höfrová; Venera Balidemaj; Mark A. Small (Springer, 2024)
Abstract Generation Alpha are the first to grow up immersed in digital technology and presumed to be wired differently than previous generations. This systematic review synthesizes the research literature on what has been learned so far and broadly answers the following question: What is happening in the education and training of Generation Alpha? The literature review was conducted based on guidelines outlined by The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Titles of 2,093 studies, abstracts of 603 studies, and 335 full-text studies were evaluated for inclusion criteria. A total of 83 studies were included into the literature review. The studies were sorted into four major categories: (1) the role of teachers, (2) the role of new approaches to education, (3) the role of teaching tools, and (4) the role of blended/online learning. Despite frequent use of the term "Generation Alpha" in the research literature, relatively few studies report generational differences that reveal how children of this generation are characteristically different from previous generations. There is simply a strong assumption that Generation Alpha is different. A major concern is that the use of technology by Generation Alpha has decreased opportunities for social-emotional development and increased mental health problems. There are digital educational tools and online strategies being developed and tested but none have emerged to be dominant.